Association of diabetes, hypertension, and their combination with basal symptoms and treatment responses in overactive bladder patients - Müderrisoglu, A. Elif; Sakul, Ayse A.; Murgas, Sandra; de la Rosette, Jean J. M. C. H.; Michel, Martin C. (Frontiers in Pharmacology, 2023)
Pelvic hypoperfusion caused by atherosclerosis has been proposed as a cause of lower urinary tract dysfunction including overactive bladder syndrome (OAB). Limited data indicate that OAB patients with concomitant diabetes or hypertension, known risk factors of atherosclerosis, may exhibit greater baseline OAB symptoms and slightly smaller therapeutic responses to treatment, but the impact of a combined presence of diabetes and hypertension has not been reported. Therefore, we have explored whether the combined presence of both comorbidities is associated with greater baseline OAB symptoms than that of either comorbidity alone. Secondary questions were exploration of the impact of either comorbidity on baseline symptoms, and of the impact of either comorbidity alone and their combination on therapeutic responses. Data from two non-interventional studies applying treatment with propiverine ER 30 or 45 mg/d for 12 weeks were analyzed. Number of urgency episodes in the combination group was greater than with each comorbidity alone. The impact of comorbidities on baseline intensity of incontinence, frequency or nocturia or Patient Perception of Bladder Condition was less consistent or absent. Either comorbidity alone was associated with a smaller % improvement of symptoms, and their combination had a greater effect than either alone. However, all attenuations associated with comorbidity were small relative to the overall improvement. We conclude that comorbidities of diabetes and hypertension have detectable effects on OAB symptoms and treatment responses, but the small magnitude of these alterations does not justify changing existing paradigms for the clinical management of OAB.